"Mathematics self-efficacy, test anxiety and attitude towards mathematics: relationship to mathematics achievement among secondary school students " (2010)
"The study examined the relationship among mathematics self-efficacy, test anxiety and attitude towards mathematics on mathematics achievement of secondary school students. A sample of 200 senior secondary school 2 (552) students participated. Their age ranged between 12 and 17 years with mean age of 14.5 years. Data collected involved the use of three valid and reliable instruments to assess mathematics self-efficacy, test anxiety and attitude towards mathematics while mathematics achievement test was used as a measure of achievement. Multiple regression analysis was used to treat the data. The results obtained indicated that mathematics self-efficacy, attitude towards mathematics and test anxiety were potent predictors mildly associated to mathematics achievement. The implications of the findings for counselling practice, teachers and other stakeholders to promote positive attitudes towards mathematics were discussed. "